2018
DOI: 10.1111/spol.12410
|View full text |Cite
|
Sign up to set email alerts
|

Student budgets and widening participation: Comparative experiences of finance in low and higher income undergraduates at a northern red brick university

Abstract: Drawing on a thematic analysis of longitudinal qualitative data (ntotal = 118), this article takes a “whole student lifecycle” approach to examine how lower and higher income students at an English northern red brick university variously attempted to manage their individual budgets. It explores how students reconcile their income—in the form of loans, grants, and bursaries—with the cost of living. Four arenas of interest are described: planning, budgeting, and managing “the student loan”; disruptions to financ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…It has now been more than a decade since the publication of this review. In the meantime, the UK higher education landscape has experienced significant changes (Harrison, 2017;Hordósy & Clark, 2018). For example, the National Collaborative Outreach Programme has established partnerships between universities and colleges to create higher education outreach programmes for widening participation, building on the previous National Networks for Collaborative Outreach and AimHigher initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…It has now been more than a decade since the publication of this review. In the meantime, the UK higher education landscape has experienced significant changes (Harrison, 2017;Hordósy & Clark, 2018). For example, the National Collaborative Outreach Programme has established partnerships between universities and colleges to create higher education outreach programmes for widening participation, building on the previous National Networks for Collaborative Outreach and AimHigher initiatives.…”
Section: Introductionmentioning
confidence: 99%
“…Some students, in turn, make savings in the form of deposits [11]. This behavior is aimed at optimizing the budget, intertemporal selection of budget items during study periods and summer months.…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…Hordósy & Clark found that in order to achieve the goal of obtaining financial independence, students "paid" with their personal time, while the time spent on work disrupted sleep patterns, negatively affected their studies, and limited interaction with peers [11].…”
Section: Analysis Of the Literaturementioning
confidence: 99%
“…Appropriate financial support in the form of maintenance funding and financial aid for tuition are key elements of student success (Dougherty and Callender, 2017; European Commission/EACEA/Eurydice, 2017). Systems without substantive financial support provision increase the risk of students having to rely on familial contributions, or to undertake part-time work throughout their studies (Antonucci, 2016;Hordósy;Clark, 2018), meaning that students from poorer backgrounds are left with the choice of indebting their future, or paying with their time throughout the duration of their studies.…”
Section: Financing University: Public and Private Fundsmentioning
confidence: 99%